Tropical Babylons : sugar and the making of the Atlantic World, 1450-1680 - Schwartz, Stuart B. (University of North Carolina Press, 2004)
"Tropical Babylons' explores the early development of the sugar industry across the Atlantic world, using case studies from Iberia, Brazil, islands of the Caribbean & of the Atlantic itself to illustrate the differences in technology, plantation management & the social consequences of the 'sugar revolution."